Pyronaridine combined with diminazene aceturate inhibits Babesia in vitro and in vivo - Shimaa Abd El-Salam El-Sayed; Mohamed Z Sayed-Ahmed; Shaimaa Ahmed Awad Ali; Nourah Alsadaan; Nawazish Alam; Mahmoud S Alkhoudary; Ikuo Igarashi; Mohamed Abdo Rizk (Asian Pacific Journal of Tropical Biomedicine, 2024)
Objective: To evaluate the combination therapy of pyronaridine tetraphosphate and diminazene aceturate against Babesia in vitro and in vivo. Methods: Bioinformatic analysis was performed using atom pair fingerprints. An in vitro combination test was performed against Babesia bovis and Theileria equi. Moreover, the in vivo chemotherapeutic efficacy of pyronaridine tetraphosphate in combination with diminazene aceturate was investigated against the growth of Babesia microti in mice using a fluorescence inhibitory assay. Results: Pyronaridine tetraphosphate and diminazene aceturate exhibited nearly similar molecular weights. The in vitro combination of pyronaridine tetraphosphate and diminazene aceturate was synergistic on Babesia bovis and additive on Theileria equi. In addition, 5 mg/kg pyronaridine tetraphosphate combined with 10 mg/kg diminazene aceturate inhibited Babesia microti growth significantly compared with those observed after treatment with 25 mg/kg diminazene aceturate alone from day 6 post treatment to day 12 post treatment. The combination therapy also normalized the hematological parameters of infected mice. Conclusions: An oral dose of pyronaridine tetraphosphate combined with a subcutaneous dose of diminazene aceturate inhibits Babesia in vitro and in mice, suggesting it might be a new paradigm for the treatment of babesiosis.